Investigation of antimicrobial activity and morphological properties of metal coated textile surfaces - Necdet Aslan; Kenan Şentürk; Tuba Şen; Turgay Çoruhlu; İpek Vartürk; Şeker, S; Shahidi, S.; Dobrovolskiy, A.M.; Tsiolko, V.V.; Matsevich, S.V.; Keskin, S.S.; May Korachi (Вопросы атомной науки и техники, 2014)
The results of investigation antimicrobial and surface properties of the textiles metal coated by means of magnetron or the cleaning-deposition system, which is based on sequentially arranged DC anode layer accelerator and hollow cathode, are presented. The antimicrobial properties against bacteria E. coli and S. aureus of cotton and polyester/cotton textiles coated by Cu, Ti and Ag with the use of two different systems were examined and compared. Представлены результаты исследования антимикробных и поверхностных свойств тканей с металлическими напылениями, созданными при помощи магнетрона или чистяще-распылительного устройства на базе последовательно расположенных ускорителя с анодным слоем и полого катода. Определены и сопоставлены антимикробные свойства тканей из хлопка и смеси хлопок/полиэстер с напылениями из Cu, Ti и Ag, созданными с использованием двух этих устройств, против бактерий E. coli и S. aureus. Представлено результати досліджень антимікробних і поверхневих властивостей тканин з металевими напиленнями, створеними за допомогою магнетрона та чистяче-розпилювального пристрою на базі послідовно розташованих прискорювача з анодним шаром та порожнистого катода. Визначені та співставлені антимікробні властивості тканин з бавовни та суміші бавовна/поліестер з напиленнями з Cu, Ti та Ag, створених за допомогою цих пристроїв, проти бактерій E. coli та S. aureus.